To be a teacher : voices from the classroom - Henry, Eric.; Huntley, Jeff; McKamey, Corinne; Laura Harper (Thousand Oaks, Calif : Corwin Press, 1995)
Mark Twain Middle School is the setting for this story of the year-long experiences of four intern teachers. Henry, Huntley, McKamey, and Harper, students in a five-year teacher education program at Trinity University, relate their personal struggles to become the kinds of teachers they've dreamed of becoming. Among the many lessons the authors share is how they struggled to know themselves - to understand their own
Includes bibliographical references
Keywords: Student teachers -- United States -- Biography; Student teaching -- United States